Small Obstacle Avoidance Sensor - Richard H. Vollmerhausen (The Scientific World Journal)
This paper describes a laser ranging sensor that is suitable for applications like small unmanned aerial vehicles. The hardware consists of a diode emitter array and line-scan charge coupled devices. A structured-light technique measures ranges up to 30 meters for 64 field angles in a 90 degree field of view. Operation is eye safe, and the laser wavelength is not visible to night vision goggles. This paper describes a specific sensor design in order to illustrate performance for a given package size.